Retrospective Identification of a Broad IgG Repertoire Differentiating Patients With S. aureus Skin and Soft Tissue Infections From Controls - Rigat, Fabio; Bartolini, Erika; Dalsass, Mattia; Kumar, Neha; Marchi, Sara; Speziale, Pietro; Maione, Domenico; Chen, Luqiu; Romano, Maria Rosaria; Alegre, Maria-Luisa; Bagnoli, Fabio; Daum, Robert S.; et al. (Frontiers in Immunology, 2019)
Background. Although the relevance of humoral immunity for protection against S. aureus skin and soft tissue infections (SSTIs) has been suggested by several animal and human studies, the unanswered question of which human antibodies may be protective has so far impeded the development of a safe and effective vaccine. Because most adults have developed certain anti-S. aureus antibodies due to S. aureus colonization or infection, we hypothesized that the titers of antibodies to S. aureus in uninfected controls would differ from those in infected patients and would also differ in infected patients from the time of acute infection to a 40-day convalescent serum. Methods. To test these hypotheses, we measured human antibody levels against a panel of 134 unique antigens comprising the S. aureus surfome and secretome in subjects with active culture-confirmed S. aureus SSTIs (cases) and in controls with no infection, using a novel S. aureus protein microarray. Results. Most S. aureus SSTI patients (n=60) and controls (n=142) had antibodies to many of the tested S. aureus antigens. Univariate analysis showed weak differences in the IgG levels to some antigens in the SSTI patient (case) sera compared with controls. Antibody levels to most tested antigens did not significantly increase nor decrease comparing acute with 40-day serum samples. Multiple logistic regression identified a rich subset of antigens that, by their antibody levels, together correctly differentiated all cases from all controls. Conclusions. Antibodies directed against S. aureus antigens were present both in patients with S. aureus SSTIs and in uninfected control patients. SSTI patients and controls could be distinguished only based on differences in antibody levels to many staphylococcal surface and secreted antigens. Our results demonstrate that in the studied population, the levels of anti-S. aureus antibodies appear largely fixed, suggesting that there may be some level of unresponsiveness to natural infection.